Risk of hypervitaminosis in the elderly population and the role of the pharmacist (Research, Society and Development, 2022)
Intake of vitamin supplements has become not only an easily available and simple method of restoring individual vitamin deficiencies, but also a fad propagated by the media and manufacturers. Where by falling victim to this fad as well as propaganda claims, many people are convinced of the excellent reputation of taking vitamins in the form of pills or capsules and their power to fully meet their demand in a necessary and harmless way. In this sense, the present study aimed, through an integrative review, to describe the risks associated with Hypervitaminosis in elderly patients. Research studies have shown that the clinical manifestations of hypervitaminosis are generally reversible with discontinuation of treatment and slow recovery in the months after discontinuation. Although, in general, they have highlighted the importance of familiarizing physicians and pharmacists with the composition of trace elements, vitamin supplements and their respective potential toxicities associated with overdose. In this way, the pharmaceutical professional must, in addition to complying with current pharmacovigilance legislation, apply their knowledge regarding pharmaceutical care and care, performing anamnesis, clarifying doubts and seeking to assist in the rational use of medicines.